VISCOMETER DIGITAL DESIGN FOR MEASURING VISCOSITY OIL WITH MICROCONTROLLER ATMega8535 PC - nurjannah nurjannah (Saintia Fisika, 2013)
Design digital viscosimeter base on ATMEGA8535 mikrocontroller have been conducted by using ball method fall, used sampel that is cooking oil  have brand ( A), bulk cooking oil which not yet been weared ( B), bulk cooking oil once wear ( C) and glycerine. The Viscosimeter have in test-drive to determine viscositas which  its result of Oil of A = 3,16 Poise x10-3, Oil of B = 3,30 Poise x10-3, Oil of C = 3,11 Poise x10-3, and Glycerine = 1,28 Poise and by using conventional viscosimeter ( its result manual) of Oil of A = 3,40x10-3 Poise, Oil of B = 3,60 x10-3 Poise, Oil of C = 2,78x10-3 Poise, and Glycerine = 1,20 Poise. Result of from compared to digital viscosimeter of conventional viscosimeter ( manual) in the reality its result come near so that can be said that by this appliance have been able to measure cooking oil viskositas of A, B, C and glycerine. And with efficacy of scheme of this digital viskosimeter have earned to replace measurement of conducted viskositas manually the which measurement can be conducted swiftly is, accurate, and practical